Impact of the Ebola Virus Outbreak on Tuberculosis Treatment Adherence and Outcomes in a Military Hospital in Freetown, Sierra Leone (London Journal of Medical and Health Research, 2024)
Introduction: The impact and disruption of infectious disease outbreaks stretch far beyond their direct death toll, as they often overburden health systems, reduce treatment seeking behaviors, and interrupt treatment regimens. This study examines the impact of the 20142016 Ebola virus outbreak on tuberculosis (TB) treatment outcomes at the 34 Military Hospital in Freetown, Sierra Leone.Methods: We used retrospective data from 1,085 TB patient outcome data registers to build a multinomial logistic regression model to evaluate the change in TB treatment outcomes before and after the Public Health Emergency of International Concern (PHEIC) declaration in August 2014.Results: These results showed that HIV status, patient age, whether patients had active versus latent TB, and the time since the start of the outbreak were significantly associated with TB treatment outcomes.Discussion: The model showed an increase in probability of unknown and unsuccessful (died or treatment failed) treatment outcomes with each month after the PHEIC declaration, across age groups, TB status, and HIV status.
Keywords: relative length of telomeric repeats; coronary heart disease with myocardial infarction; percentage of the calibrator; oxidative stress; protective effect; chromosomes.; Human bite; soft tissue necrosis; mortality; woman; women's health; neoplasm